Peningkatan Integritas Diri Lansia Melalui Terapi Kelompok Terapeutik dan Reminiscence - Norman Wijaya Gati; Mustikasari Mustikasari; Yossie Susanti Eka Putri (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2016)
Elderly changing through time biologically, psychological and socially. The Changes experienced by the elderly will affect the lives of elderly both physically and psychologically. They need support to adapt the changes that happened in their lives. Support can be given to the elderly includes support to individuals, families and groups. The purpose of this scientific work is to describe the application of therapeutic group therapy and Reminiscence to achieve self-integrity through Stuart’s Stress Concept and Roy Adaptation Model approach. Analysis was conducted to 20 elderly who received therapeutic group therapy, therapy was continued to 10 elderly who have signs symptoms of depression with Reminiscence therapy. The result obtained there were increasing of self-integrity after following therapeutic group therapy. The other result there were decreased in depressive sign and symptoms after pollowing reminiscence therapy. Conclusion : Therapeutic Group Therapy is recomended to the elderly to help them adapt and achieve self-integrity, and Reminiscence therapy was effective to reduce sign and symptoms of depression. This Scientific Works recommends further research on the factors affecting the achievement of integrity and involvement of families and volunteers in the implementation of therapy in elderly.